Public Policy Defense and the Arbitrability of Competition Disputes Under the Philippine Arbitration Regime - James Gregory Alcaraz Villasis (Faculty of Law, Sriwijaya University, Indonesia, 2020)
The arbitrability of anti-competition disputes in the Philippines remains to be tested. It is since the Philippine Competition Act is relatively at its infancy, and cases are yet to be brought before the courts. This area entails much complexity considering that competition disputes are by nature imbued with public policy concerns, a mandatory exception for arbitration. This paper aims to examine the arbitrability of competition disputes under the Philippine domestic arbitration regime. After conducting an examination of cases and literature both in the Philippines and abroad, the paper argues that the Philippines may consider the US and French positions as to the arbitrability of competition disputes despite the presence of various public policy concerns. The public policy issues should only be taken into consideration when an arbitral award is brought before judicial bodies for recognition and enforcement and should not bar domestic arbitral bodies from taking cognizance of these disputes. It is to accommodate the state policy regarding alternative means of settling disputes such as arbitration in rendering speedy administration of justice. Whenever an award is granted, the same will be subject to court's intervention for recognition with due respect to the public policy concerns. In so doing, arbitration is being promoted without sacrificing the competition law policy of the Philippines.